Lithium-based negative electrode and preparation method thereof, and lithium metal battery
Patent Information
- Application Number
- CN202611047375.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-13
AI Technical Summary
但是亲锂材料在长循环过程中,通常会因与锂发生反应而不可避免地发生粉碎和团聚
1、本发明通过亲锂性颗粒、功能添加剂与聚合物粘结剂的相互作用:亲锂性颗粒能提供高密度均匀亲锂位点,显著降低锂成核势垒,引导锂均匀沉积以抑制枝晶生长,功能添加剂形成的金属-有机硅层,可保证锂离子均匀传输,并增强界面黏附,聚合物粘结剂则能牢固结合亲锂性颗粒与基底、隔膜,有效避免循环过程中颗粒脱落和无涂层体相锂暴露,最终使锂金属负极兼具高倍率性能与长循环稳定性。
Smart Images

Figure CN122907594A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a lithium-based anode and its preparation method, and a lithium metal battery. Background Technology
[0002] Lithium metal, due to its high theoretical specific capacity (3860 mAh / g) and low redox potential (-3.04 V vs SHE), is a core anode material for next-generation high-energy-density batteries. Compared to designs without an anode, lithium metal anodes with limited thickness can significantly improve battery cycle life. However, when lithium metal comes into contact with the electrolyte, a solid electrolyte film composed of electrolyte decomposition products forms on its surface. This film typically has an inhomogeneous structure and is prone to cracking and breakage during long cycles, leading to localized lithium dendrite deposition. When dendrites grow to the cathode, it increases the risk of short circuits and shortens cycle life, becoming a key bottleneck restricting its industrialization. To address the lithium dendrite problem, lithiophilic modification techniques have been widely studied: by introducing lithiophilic materials onto the anode surface, the lithium nucleation barrier is lowered, inducing uniform lithium deposition and thus suppressing dendrite growth. However, lithiophilic materials inevitably pulverize and agglomerate during long cycles due to reactions with lithium. Therefore, how to optimize the lithium-based anode of lithium metal batteries to improve cycle life has become a pressing technical challenge for those skilled in the art. Summary of the Invention
[0003] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a lithium-based anode and its preparation method, and a lithium metal battery. Through the interaction of lithiophilic particles, functional additives, and polymer binders, the lithium nucleation barrier is reduced, guiding uniform lithium deposition to suppress dendrite growth, thus enabling the lithium metal battery to possess both high rate performance and long cycle stability.
[0004] To solve the above-mentioned technical problems, the present invention is implemented as follows: According to one aspect of the present invention, a lithium-based anode is provided, comprising a substrate and a lithiophilic modification layer located on at least one side surface of the substrate along the thickness direction; The lithiophilic modification layer comprises lithiophilic particles, a polymer binder, and functional additives; The functional additives include organosiloxanes containing unsaturated bonds.
[0005] In some embodiments, the lithium-based anode includes one or more of Si-O-Li bonds, Si-O-Si bonds, and Si-OC bonds.
[0006] In some of these embodiments, the peel strength of the lithiophilic modified layer is ≥50 N / m.
[0007] In some embodiments, the lithiophilic particles include one or more of the following: gold, silver, zinc, magnesium, aluminum, platinum, tin, bismuth, antimony, magnesium nitride, aluminum nitride, calcium nitride, titanium nitride, zirconium nitride, vanadium nitride, and tungsten nitride.
[0008] In some embodiments, the lithiophilic particles comprise secondary particles composed of primary particles.
[0009] In some embodiments, the polymer binder includes one or more of polyethylene oxide, styrene-butadiene rubber, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, and polyvinyl butyral.
[0010] In some of these embodiments, the main chain of the functional additive contains unsaturated bonds.
[0011] In some embodiments, the functional additive includes an alkoxy group, and the alkoxy group is bonded to a silicon atom.
[0012] In some of these embodiments, the Dn50 of the secondary particles is 0.6 μm to 0.8 μm.
[0013] In some of these embodiments, the Dn50 of the primary particle is 60 nm to 200 nm.
[0014] In some of these embodiments, the main chain comprises 2 to 5 carbon atoms.
[0015] In some of these embodiments, the silicon atom is bonded to three of the alkoxy groups.
[0016] In some of these embodiments, the alkoxy group comprises 1 to 2 carbon atoms.
[0017] In some embodiments, the mass ratio of the lithiophilic particles, the polymer binder, and the functional additive is (80~95):(1~10):(1~10).
[0018] In some embodiments, the thickness of the lithiophilic modification layer is 0.3 μm to 1.8 μm.
[0019] In some embodiments, the thickness of the substrate is 10 μm to 100 μm.
[0020] In some of these embodiments, the substrate comprises metallic lithium or a lithium alloy.
[0021] According to another aspect of the present invention, the present invention provides a method for preparing the lithium-based anode described in the above technical solution, comprising the following steps: A lithiophilic particle, a polymer binder, a functional additive, and an organic solvent are mixed to obtain a lithiophilic modified solution; the functional additive includes an organosiloxane containing unsaturated bonds. The lithiophilic modification solution is coated onto at least one side of the substrate along the thickness direction, and after drying, a lithium-based anode is obtained.
[0022] In some embodiments, the lithiophilic particles, polymer binder, functional additives and organic solvent are mixed and stirred at 25°C to 55°C to form a lithiophilic modified solution; the stirring is carried out at a speed of 200 rpm to 600 rpm for 10 min to 30 min.
[0023] In some embodiments, the solid content of the lithiophilic modified solution is 45% to 80%.
[0024] In some of these embodiments, the coating includes electrostatic spraying and / or ultrasonic spraying.
[0025] In some embodiments, the drying includes a first drying and a second drying performed sequentially; the temperature of the first drying is 60°C to 100°C and the time is 20 min to 60 min; the temperature of the second drying is 100°C to 120°C and the time is 10 min to 30 min.
[0026] According to another aspect of the present invention, the present invention provides a lithium metal battery, comprising a lithium-based anode as described in the above technical solution or a lithium-based anode prepared by the preparation method described in the above technical solution.
[0027] In some embodiments, the lithium metal battery further includes an electrolyte; the electrolyte includes an electrolyte salt, a solvent, and additives.
[0028] In some embodiments, the electrolyte salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalate borate, and lithium di(oxalate borate).
[0029] In some embodiments, the solvent includes one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethyl ether, triethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, and fluorinated 1,3-dioxolane.
[0030] In some embodiments, the additive includes one or more of lithium nitrate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl fluorocarbonate, trimethyl phosphate, and triethyl hexafluorophosphate.
[0031] Implementing the technical solution of the present invention has at least the following beneficial effects: 1. This invention utilizes the interaction between lithiophilic particles, functional additives, and polymer binders: lithiophilic particles provide high-density, uniform lithiophilic sites, significantly reducing the lithium nucleation barrier and guiding uniform lithium deposition to suppress dendrite growth; the metal-organosilicon layer formed by functional additives ensures uniform lithium ion transport and enhances interfacial adhesion; and the polymer binder firmly binds the lithiophilic particles to the substrate and separator, effectively preventing particle shedding and exposure of uncoated bulk lithium during cycling, ultimately enabling the lithium metal anode to possess both high rate performance and long-cycle stability.
[0032] 2. Addressing the pain points of existing lithium metal anode lithium-ion modification technologies, such as complex and costly modification layer preparation processes, weak interfacial adhesion leading to easy detachment and performance degradation, and difficulty in large-scale production, this invention further improves upon these limitations. By precisely controlling the particle size distribution and volumetric filling rate of nanoscale lithium-ion particles, combined with the synergistic effect of functional additives and polymer binders, and employing simple and cost-effective electrostatic spraying or ultrasonic spraying techniques, a lithium-ion modification layer with a thickness of only 0.3μm to 1.8μm has been successfully prepared. This avoids the adverse effects of traditional micron-level coatings on energy density and rate performance, and allows for large-scale preparation of nanoscale coatings without relying on high-end equipment such as PVD and CVD, significantly improving the practicality and industrial applicability of lithium metal batteries.
[0033] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0034] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0035] Figure 1 This is a schematic diagram of a lithium-based anode provided in an embodiment of the present invention.
[0036] Figure 2 A scanning electron microscope image of a lithium-based anode with a lithiophilic modification layer provided in Embodiment 1 of the present invention.
[0037] Figure 3 XPS spectrum of lithium-based anode with a lithiophilic modification layer provided in Embodiment 1 of the present invention.
[0038] The accompanying drawings have illustrated specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0039] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0040] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0041] In the description of this application, "same chemical composition" should be interpreted broadly, that is, the main components of the two have the same chemical composition, or the two have substantially the same chemical composition, but may have errors or impurities within the acceptable range that can be understood by those skilled in the art.
[0042] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.
[0043] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0045] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0046] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0047] Currently, the structural integrity of the lithiophilic components and carrier materials is crucial for preparing stable lithium metal composite anodes and achieving uniform lithium deposition and stripping. Existing technologies, such as the solid-liquid hybrid system (using a high-concentration electrolyte) from SES in Massachusetts, can partially suppress dendrite formation, but do not address the lithiophilic modification of the lithium metal anode. CATL and Samsung SDI's all-solid-state electrolyte routes can improve safety through solid-solid interface optimization, but face challenges such as high interface impedance and the difficulty in mass-producing brittle materials. Jinyu New Energy's three-dimensional host material route can disperse lithium deposition stress, but the additional weight of the three-dimensional current collector weakens the energy density advantage, and the complex process restricts mass production. In addition, Chinese patent CN112216811A uses electrospinning to prepare a lithiophilic fiber layer on the surface of copper foil. Although this can improve lithium deposition, the electrospinning process is complex and costly, making it difficult to scale up production. Chinese patent CN115347196A optimizes lithiophilicity by constructing a three-dimensional porous current collector, but the porous structure is difficult to prepare, has poor production consistency, and is prone to uneven electrolyte wetting, making it difficult to scale up production. Chinese patent CN114649502A uses liquid metal coating modification, but liquid metal is expensive, making it difficult to scale up production. In summary, existing technologies generally use methods such as drop coating, roll coating, immersion, PVD, CVD, ALD, and magnetron sputtering to create a complete lithiophilic modification layer on the surface of a lithium metal substrate; however, the following problems still exist: (1) The thickness of the lithium-loving modification layer prepared by commonly used methods such as drop coating and immersion is usually in the micrometer range, which sacrifices the actual mass and volumetric energy density of the lithium metal anode; and although the complete coating improves the uniform deposition of lithium metal, it also affects the rate performance of lithium metal batteries.
[0048] (2) Although nanoscale thicknesses can be obtained by PVD, CVD, ALD, magnetron sputtering and other methods, these methods usually involve large equipment investment, low production efficiency, complex processes and high costs, and are not suitable for large-scale industrial production.
[0049] (3) The complete coating prepared by the prior art is applied to the surface of the lithium metal substrate. The interface bonding force between the modified layer and the substrate is weak. It is easy to fall off during the volume expansion / contraction cycle of long-term charge and discharge, resulting in the failure of lithium-loving sites, rapid capacity decay, and weakening of dendrite suppression effect. As the cycle continues, the original bulk lithium is continuously corroded, and the non-dense deposited lithium will be pulverized, resulting in the uncoated bulk lithium being exposed in the electrolyte, leading to a cliff-like decline in battery performance.
[0050] Based on this, the present invention addresses the key issues restricting the practical application of lithium metal anodes. With optimized lithiophilic modification technology as its core approach, it lowers the lithium nucleation barrier through the interaction of lithiophilic particles, functional additives, and polymer binders, guiding uniform lithium deposition to suppress dendrite growth. This enables lithium metal batteries to possess both high rate performance and long cycle stability. Furthermore, by controlling the particle size distribution of lithiophilic particles and optimizing spraying parameters to control the thickness of the modification layer, the composition and structure of the lithiophilic modification layer are optimized. Ultimately, this invention provides a lithium metal anode modification scheme that promotes uniform lithium metal deposition, exhibits high rate performance and long cycle stability, and is simple to process and suitable for large-scale production. Specifically, the present invention adopts the following technical solution: According to one aspect of the present invention, a lithium-based anode is provided, comprising a substrate and a lithiophilic modification layer located on at least one side surface of the substrate along the thickness direction; The lithiophilic modification layer comprises lithiophilic particles, a polymer binder, and functional additives; The functional additives include organosiloxanes containing unsaturated bonds.
[0051] In this invention, the lithium-based anode comprises a substrate and a lithiophilic modification layer (hereinafter referred to as the modification layer), preferably composed of a substrate and a lithiophilic modification layer; wherein, the substrate preferably comprises metallic lithium or a lithium alloy, specifically it can be: lithium metal strip or lithium alloy strip (such as copper-lithium composite strip); this invention does not have any special restrictions on the source of the substrate, and commercially available products well known to those skilled in the art can be used.
[0052] In a specific embodiment of the present invention, the thickness of the substrate is preferably 10μm to 100μm, specifically 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, or any value between the two mentioned above. It should be noted that if the substrate thickness is too large, it will reduce the battery energy density; while if the substrate thickness is too small, the mechanical strength of the negative electrode will be too low, and during cycling, with volume changes, it may cause electrode breakage, resulting in decreased safety and stability.
[0053] In this invention, the lithiophilic modification layer is located on at least one side surface of the substrate along the thickness direction; the lithiophilic modification layer includes lithiophilic particles, a polymer binder, and functional additives; wherein, the lithiophilic particles can reduce the lithium nucleation barrier, induce uniform lithium deposition, avoid uneven thickness of the SEI due to local current concentration, and provide suitable lithium metal nucleation sites; the polymer binder, as a "skeleton reinforcing agent," can firmly bind the lithiophilic particles to the substrate and the separator through molecular chain entanglement and interfacial adsorption, inhibit interlayer separation between the modification layer and the substrate, and prevent particle shedding during cycling, thereby ensuring the structural stability of the lithiophilic modification layer; the functional additives include organosiloxanes containing unsaturated bonds, which can undergo addition reactions with the unsaturated double bonds in the polymer binder to form CC single bonds, and the -hydroxyl (OH) in the polymer binder, in synergy with the alkoxy group of the siloxane, undergoes a silanol condensation reaction to form Si-OC bonds, further forming a flexible organosilicon modification layer with a three-dimensional porous structure, significantly improving the mechanical strength and interfacial adhesion of the modification layer.
[0054] Based on this, the three components of lithiophilic particles, polymer binders, and functional additives jointly construct a multi-level structure of "rigid particle support - flexible silane filling - polymer binder reinforcement" (see [reference]). Figure 1 (As shown in the image). The advantages of this structure are: firstly, the retained submicron pores improve electrolyte wettability and liquid retention, solving the problem of easy agglomeration and accumulation of single particles; secondly, the flexible siloxane network can adjust the interfacial charge distribution, ensuring uniform lithium-ion transport and buffering volume expansion during lithium deposition / stripping, avoiding cracking of the modification layer during long cycling; thirdly, the submicron-thick modification layer ensures low interfacial impedance and high lithium-ion mobility and migration number without losing too much energy density, preventing lithium-ion depletion on the substrate surface and the growth of lithium dendrite tips. This submicron three-dimensional porous composite structure makes the modification layer less prone to interlayer separation due to volume changes during lithium deposition / stripping during cycling, solving the problem of single-component modification layers easily pulverizing and falling off during long cycling; at the same time, the use of the above-mentioned submicron-level lithiophilic modification layer can perform lithiophilic modification on lithium metal / alloy substrates, actively guiding lithium deposition and fundamentally inhibiting lithium dendrite growth, thereby obtaining good long-cycle performance.
[0055] In a specific embodiment of the present invention, the lithium-based anode preferably includes one or more of Si-O-Li bonds, Si-O-Si bonds, and Si-OC bonds, more preferably Si-O-Li bonds. It should be noted that the reason for including Si-O-Li bonds in the lithium-based anode is that the RO-Si of the organosiloxane containing unsaturated bonds undergoes a hydrolysis reaction with the Li on the lithium metal substrate and the adsorbed trace amounts of water to generate silanol. The silanol further reacts with the lithium metal substrate to generate Si-O-Li covalent bonds; or the silanol undergoes a condensation crosslinking reaction. The metal-organosilicon flexible modification layer formed by the above hydrolysis and condensation reactions is fixed to the lithium metal substrate by covalent bonds, which can ensure uniform lithium ion transport and buffer the volume expansion caused by lithium metal deposition.
[0056] In a specific embodiment of the present invention, the peel strength of the lithiophilic modified layer is preferably ≥50 N / m.
[0057] In specific embodiments of the present invention, the lithiophilic particles preferably include one or more of the following: gold, silver, zinc, magnesium, aluminum, platinum, tin, bismuth, antimony, magnesium nitride, aluminum nitride, calcium nitride, titanium nitride, zirconium nitride, vanadium nitride, and tungsten nitride. It should be noted that the metal elements in the lithiophilic particles can form coordination bonds with the oxygen and nitrogen atoms in the siloxane, further strengthening the chemical bond and preventing the aggregation or shedding of the lithiophilic particles. In a preferred embodiment of the present invention, the lithiophilic particles are the aforementioned metal nitrides; when these metal nitrides come into contact with lithium metal, they can form an electronically insulating lithium-containing nitride mesophase to passivate the interface, such as Li3N, which has been proven to be a beneficial high-strength inorganic component in an SEI.
[0058] In a specific embodiment of the present invention, the lithiophilic particles preferably comprise secondary particles composed of primary particles; wherein, the Dn50 of the secondary particles is preferably 0.6μm~0.8μm, specifically 0.6μm, 0.7μm, 0.8μm, or any value between the two mentioned above; if it is too large, that is, the particle size distribution of the secondary particles is uneven, the particles are poorly packed, and they are easy to fall off. Moreover, large particles may approach or even exceed the thickness range of the modification layer, causing local protrusions on the surface of the modification layer, which may induce local current concentration, causing lithium ions to accumulate in the lithiophilic particles. The top deposition and induction of lithium dendrite tip growth are too small. The uniform particle size cannot buffer the volume expansion stress during lithium deposition / stripping through gradient stacking, reducing the flexibility of the modification layer and making it prone to cracking due to stress concentration during cycling. In addition, the particle size distribution is too narrow, which will reduce the particle dispersion stability during spray coating and easily cause "bridging and agglomeration", resulting in local dense agglomerates or voids in the modification layer. The volume filling rate of lithiophilic particles in the modification layer is too low. Although the distribution of lithiophilic sites is uniform, the density is insufficient, which cannot fully disperse the current density and affect the uniform lithium deposition effect.
[0059] In a specific embodiment of the present invention, the Dn50 of the primary particles is preferably 60nm~200nm, specifically 60nm, 100nm, 150nm, 200nm, or any value between the two mentioned above. If the particle size of the primary particles is too large, the specific surface area is significantly reduced, the number of lithium-affinity active sites is reduced, and the core advantage of the low lithium nucleation barrier of the nanoparticles cannot be fully utilized, resulting in poor uniformity of lithium deposition. If the particle size of the primary particles is too small, the specific surface area increases sharply, and the tendency to agglomerate is extremely strong. Even if they are assembled into secondary particles, secondary agglomeration is likely to occur during spraying dispersion or cycling, which will destroy the uniformity and porous network of the secondary particles, leading to local densification or defects in the modified layer.
[0060] It should be noted that the secondary particles composed of the above-mentioned nanoscale primary particles in this invention not only retain the abundant lithium-loving active sites brought by the high specific surface area of the nanoscale primary particles, which can significantly reduce the lithium nucleation barrier and guide the uniform deposition of lithium, but also form a porous network adapted to the thickness of the modification layer through the stacking of secondary particles, ensuring electrolyte wetting and rapid lithium ion transport, while improving the mechanical strength and spray coating film-forming properties of the modification layer, and avoiding the particles from falling off or agglomerating due to lithium volume changes during cycling.
[0061] In a specific embodiment of the present invention, the aggregation index of the lithiophilic particles (Dn50 of secondary particles / Dn50 of primary particles) is preferably 3 to 15. If it is too large, the secondary particles will aggregate excessively, leading to a decrease in the porosity of the modified layer and uneven distribution of lithiophilic particles. This not only disrupts the continuity and consistency of the porous structure of the modified layer, causing lithium-ion transport to be hindered and uneven distribution of lithiophilic sites, but also causes stress concentration inside the secondary particles, resulting in decreased mechanical stability and easy crushing and cracking during cycling. If it is too small, the size difference between the secondary particles and the primary particles is small, making it difficult to form an effective porous network. This leads to densification of the modified layer, increased ion transport impedance, and excessive dispersion of the nano-primary particles with a large specific surface area. During spray coating, these particles are prone to agglomeration, forming local defects and affecting the uniformity of lithiophilic guidance and the structural stability of the modified layer.
[0062] In specific embodiments of the present invention, the polymer binder preferably includes one or more of the following: polyethylene oxide (PEO), styrene-butadiene rubber (SBR), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), and polyvinyl butyral (PVB). The present invention does not impose any particular restrictions on the source of the polymer binder; commercially available products well-known to those skilled in the art can be used.
[0063] In a specific embodiment of the present invention, the main chain of the functional additive preferably contains unsaturated bonds; specifically, the functional additive preferably includes alkoxy groups, and the alkoxy groups are linked to silicon atoms, such as 3-butenyltrimethoxysilane. It should be noted that the siloxy groups undergo hydrolysis-condensation reactions with the lithium metal substrate Li and the trace amounts of water adsorbed on its surface to generate Li-O-Si bonds; the longer organic main chain containing unsaturated bonds can form a flexible three-dimensional network during crosslinking, and can improve the adsorption and wetting properties of the electrolyte.
[0064] In a specific embodiment of the present invention, the main chain preferably comprises 2 to 5 carbon atoms. The cross-linked network formed by a slightly longer organic main chain can provide more space to accommodate nanoscale lithium-loving particles; the long carbon chain can increase the steric hindrance and flexibility of silane molecules, which can avoid particle agglomeration caused by excessive cross-linking of short main chains, and can also provide uniform dispersion sites for primary particles through the spatial extension of chain segments; if the carbon chain is too long, it will reduce the cross-linking density, resulting in insufficient mechanical strength of the modified layer, which cannot resist the volume expansion stress of lithium deposition / stripping, and may also affect electrolyte wetting and lithium ion transport due to excessive molecular chain entanglement.
[0065] In a specific embodiment of the present invention, the silicon atom is preferably bonded to three alkoxy groups; the alkoxy groups preferably include one to two carbon atoms. The preferred number of alkoxy groups bonded to the silicon atom is three, which ensures a suitable bonding force between the modified layer and the lithium metal substrate; simultaneously, excessively long carbon chain lengths of the alkoxy groups lead to a significant decrease in the hydrolysis rate; based on this, the present invention employs the aforementioned suitable range to ensure that the functional additives achieve good overall interaction with other components.
[0066] In a preferred embodiment of the present invention, the functional additive is preferably selected from one or more modified silanes such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, allyltrimethoxysilane, allyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-butenyltrimethoxysilane, 3-butenyltriethoxysilane, 4-mercapto-2-butenyltrimethoxysilane, 4-mercapto-2-butenyltriethoxysilane, 3-amino-1-butenyltriethoxysilane, tris(trimethylsilyl)phosphite, 4-pentenyltrimethoxysilane, 2-methyl-3-mercaptopentyltrimethoxysilane, and 4-(trimethylsiloxy)-3-penten-2-one. The present invention does not impose any special restrictions on the source of the functional additive; commercially available products well known to those skilled in the art can be used.
[0067] In a specific embodiment of the present invention, the preferred mass ratio of the lithiophilic particles, the polymer binder, and the functional additives is (80~95):(1~10):(1~10). It should be noted that too many lithiophilic particles result in insufficient proportions of polymer binder and functional additives in the modified layer, leading to decreased adhesion and mechanical strength, and increased susceptibility to cracking and detachment during cycling; reduced battery energy density; and too few lithiophilic particles result in insufficient lithiophilic active sites, failing to effectively lower the lithium nucleation barrier, hindering uniform lithium deposition, and increasing the risk of lithium dendrite growth; furthermore, the modified layer lacks sufficient support and is prone to collapse. Too much polymer binder will extensively cover the active sites on the surface of the lithiophilic particles, significantly increasing interfacial impedance; too little polymer binder cannot adequately achieve a strong bond between the lithiophilic particles, functional additives, and the substrate, making the modified layer susceptible to particle detachment and interlayer separation under the volumetric stress of lithium deposition / stripping, resulting in loss of structural stability. Too many functional additives can lead to excessive siloxanes reacting with the electrolyte, resulting in an overly thick SEI film and increased interfacial impedance. Too few functional additives can result in insufficient adhesion and flexibility between the modified layer and the lithium metal substrate, making it prone to interlayer separation during cycling and failing to achieve the desired interface optimization and structural stability.
[0068] In a specific embodiment of the present invention, the thickness of the lithiophilic modification layer is preferably 0.3 μm to 1.8 μm, specifically 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 1.8 μm, or any value between the two mentioned above. It should be noted that if the thickness of the lithiophilic modification layer is too large, it reduces the battery energy density and increases the interface impedance, affecting rate performance. Conversely, if the thickness of the lithiophilic modification layer is too small, the lithium-ion deposition thickness will prematurely exceed the modification layer thickness, resulting in subsequent lithium-ion tip deposition on top of the deposited lithium, and the modification layer will lose its lithiophilic modification effect.
[0069] In this invention, the lithium-based anode comprises a substrate and a lithiophilic modification layer located on at least one side of the substrate along its thickness direction. The lithiophilic modification layer comprises lithiophilic particles, a polymer binder, and functional additives. The polymer binder interacts with other components in multiple ways: firstly, it acts as a "skeleton reinforcing agent" distributed at the organosilicon network nodes, and through molecular chain entanglement and interfacial adsorption, it firmly bonds the lithiophilic particles to the substrate and separator, inhibiting interlayer separation between the modification layer and the substrate, preventing particle shedding during cycling, and thus ensuring the structural stability of the lithiophilic modification layer; secondly, during the preparation of the lithiophilic modification layer, the polymer binder can improve the dispersion stability of the modification solution, prevent the agglomeration of lithiophilic particles during stirring, ensure atomization uniformity during spraying, and ensure precise control of the submicron-level modification layer thickness, adapting to the needs of large-scale production; thirdly, the solvent system of the fluorinated ether-based electrolyte used subsequently can synergistically complex Li with the ether bonds, hydroxyl carboxyl groups, amide groups, and other functional groups of the polymer binder in the modification layer. +Alternatively, Li⁺ can be stabilized and solvated through hydrogen bonding / dipole interaction, reducing the association between Li⁺ and anions, increasing the number of effective charge carriers, and thus improving conductivity, thereby reducing interfacial impedance drift.
[0070] According to another aspect of the present invention, the present invention provides a method for preparing the lithium-based anode described in the above technical solution, comprising the following steps: A lithiophilic particle, a polymer binder, a functional additive, and an organic solvent are mixed to obtain a lithiophilic modified solution; the functional additive includes an organosiloxane containing unsaturated bonds. The lithiophilic modification solution is coated onto at least one side of the substrate along the thickness direction, and after drying, a lithium-based anode is obtained.
[0071] The present invention first mixes lithiophilic particles, polymer binder, functional additives and organic solvent to obtain a lithiophilic modified solution.
[0072] In this invention, the lithiophilic particles, polymer binder, and functional additives are the same as those described in the above technical solutions, and will not be repeated here; the organic solvent is preferably selected from at least one of diethyl ether, benzene, toluene, acetone, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), N-methylpyrrolidone (NMP), and N,N-dimethylformamide; this invention does not have any special restrictions on the source of the organic solvent, and commercially available products well known to those skilled in the art can be used.
[0073] In a specific embodiment of the present invention, the lithiophilic particles, polymer binder, functional additives, and organic solvent are mixed and preferably stirred at 25°C to 55°C to form a lithiophilic modification solution; the stirring is preferably carried out at a speed of 200 rpm to 600 rpm for 10 min to 30 min. In the present invention, the polymer binder can improve the dispersion stability of the modification solution during the preparation process, prevent the agglomeration of lithiophilic particles during the above stirring process, ensure the atomization uniformity of subsequent spraying, and ensure precise control of the modification layer thickness, thereby adapting to the needs of large-scale production.
[0074] In a specific embodiment of the present invention, the solid content of the lithiophilic modified solution is preferably 45% to 80%, specifically 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or any value between the two mentioned above.
[0075] After obtaining the lithiophilic modification solution, the present invention coats the lithiophilic modification solution onto at least one side of the substrate along the thickness direction, and obtains a lithium-based anode after drying.
[0076] In a specific embodiment of the present invention, the coating preferably includes electrostatic spraying and / or ultrasonic spraying; the purpose of adopting the above coating method is to ensure that the lithiophilic modification solution can be uniformly sprayed onto the substrate surface.
[0077] In a specific embodiment of the present invention, the drying preferably includes a first drying and a second drying performed sequentially; the temperature of the first drying is 60℃~100℃, and the time is 20min~60min; the temperature of the second drying is 100℃~120℃, and the time is 10min~30min. The present invention employs the above-mentioned segmented heating and drying process to ensure that a lithium-based anode that meets performance requirements is ultimately obtained.
[0078] The preparation method provided by this invention is simple, easy to control, and has mild conditions, and has broad application prospects.
[0079] According to another aspect of the present invention, a lithium metal battery is provided, comprising a lithium-based anode as described in the above-described technical solution or a lithium-based anode prepared by the preparation method described in the above-described technical solution. Thus, the lithium metal battery possesses all the features and advantages of the lithium-based anode described in the above-described technical solution, which will not be repeated here.
[0080] In this invention, the lithium metal battery includes not only the lithium-based negative electrode described in the above technical solution, but also a positive electrode, a separator, and an electrolyte. Conventional technical solutions for positive electrodes, separators, and electrolytes known to those skilled in the art for lithium metal batteries can be used.
[0081] In a specific embodiment of the present invention, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector along the thickness direction; wherein, the positive electrode current collector may be a metal foil, a foamed metal, or a composite current collector. For example, as a metal foil, silver-surfaced aluminum or stainless steel, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, or titanium, etc., may be used; the foamed metal may be foamed nickel, foamed copper, foamed aluminum, foamed alloy, etc.; the composite current collector may include a polymer material base layer and a metal layer, and the composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0082] In a specific embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material. The present invention does not impose any particular limitation on the specific type of the positive electrode active material; any active material known in the art that can be used as the positive electrode of a battery cell can be used. Those skilled in the art can select according to actual needs. Specifically, the positive electrode active material may include, but is not limited to, at least one of lithium transition metal oxides, lithium phosphates with an olivine structure, and their respective modified compounds; examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds; examples of lithium phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and their modified compounds. These materials are all commercially available.
[0083] In specific embodiments of the present invention, the positive electrode active material layer may also include a positive electrode binder, a positive electrode conductive agent, and other optional additives. As examples, the positive electrode binder may include at least one of styrene-butadiene rubber (SBR), waterborne acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB); the positive electrode conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers. These materials are all commercially available.
[0084] In a specific embodiment of the present invention, the preparation method of the positive electrode sheet adopts the method known to those skilled in the art: first, the raw materials are mixed in a solvent in a certain proportion to form a slurry, and then the positive electrode slurry is coated on the positive electrode current collector. After drying, pressing and other processes, the positive electrode sheet can be obtained.
[0085] In a specific embodiment of the present invention, the separator can be any commercially available separator known to those skilled in the art for battery manufacturing, including but not limited to at least one of polyethylene (PE) film, polypropylene (PP) film, polyimide (PI) film, and polypropylene-polyethylene composite film.
[0086] In this invention, the diaphragm is disposed between the positive and negative electrodes, mainly to prevent short circuits between the positive and negative electrodes, while allowing ions to pass through; the electrolyte plays the role of conducting ions between the positive and negative electrodes.
[0087] In a specific embodiment of the present invention, the electrolyte preferably comprises an electrolyte salt, a solvent, and additives; wherein, the electrolyte salt preferably comprises one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluorosulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiDFOB), and lithium bis(oxalate borate) (LiBOB); the solvent preferably comprises diethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (Diglyme), diethyl ether (DEE), triethylene glycol dimethyl ether (Triglyme), 1,3-dioxolane (DOL), tetrahydrofuran (THF), and 2-methyltetrahydrofuran (2-MeTHF). The additives are selected from one or more of the following: 1,4-dioxane (DIOX), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (HFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), 2,2,2-trifluoroethyl ether (TFE), bis(2,2,2-trifluoroethyl) ether (BTFE), and fluoro1,3-dioxane (F-DOL); the additives preferably include one or more of lithium nitrate (LiNO3), vinylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl fluorocarbonate (FEMC), trimethyl phosphate (TMP), and triethyl hexafluorophosphate (TEPF). The present invention does not impose any special restrictions on the source of the electrolyte salts, solvents, and additives; commercially available products well known to those skilled in the art can be used.
[0088] In a preferred embodiment of the present invention, the solvent is a fluorinated ether-based solvent, which can synergistically complex Li⁺ with functional groups such as ether bonds, hydroxy carboxyl groups, and amide groups of the polymer binder in the modified layer, or stabilize and solvate Li⁺ through hydrogen bonding / dipole interaction, reduce the association of Li⁺ with anions, increase the number of effective charge carriers, thereby improving conductivity and reducing interfacial impedance drift.
[0089] The present application will be described in detail below with reference to the accompanying drawings and embodiments. However, the implementation and protection of the present invention are not limited thereto. The following embodiments are only some embodiments of the present application and are not intended to limit the present application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0090] Example 1 1. Anode preparation: (1) Preparation of lithiophilic modified solution: Nano-sized titanium nitride was selected as the lithiophilic particles, with secondary particle Dn50=0.78μm, aggregation index=6.5, and specific surface area of 24.7m². 2 / g, accounting for 90% by weight; the polymer binder is PVDF-HFP, accounting for 5% by weight; the functional additive is 3-butenyltrimethoxysilane, accounting for 5% by weight. The above components are dispersed in NMP organic solvent and stirred at 400 rpm for 20 min at 40 °C to form a uniform lithiophilic modified solution with a solid content of 62.5%.
[0091] (2) Substrate selection: lithium metal strip, thickness 80μm.
[0092] (3) Spraying and drying: The lithium-loving modification solution obtained in step (1) is uniformly sprayed onto the substrate surface in step (2) by electrostatic spraying; the blower drying adopts a segmented heating process, first drying at 80℃ for 40 min, and then heating to 110℃ for 20 min to form a lithium-loving modification layer with a thickness of 1.05 μm, thus obtaining the target lithium-based anode.
[0093] The scanning electron microscope image of the lithium-based anode with a lithiophilic modified layer provided in Example 1 was obtained through testing. (See attached image.) Figure 2 As shown, the lithiophilic particles are uniformly dispersed with only a small number of local aggregates. This arrangement promotes the uniform distribution and nucleation of lithium ions. Additionally, the XPS spectrum of the lithium-based anode with the lithiophilic modification layer provided in Example 1 can be found in [reference needed]. Figure 3 As shown, XPS reveals a strong Si 2p peak, with the 103.6 eV peak attributed to Si-O-Si, the 102.5 eV peak attributed to Si-OC, and the 101.8 eV peak attributed to Si-O-Li, indicating that a metal-organosilicon flexible modification layer has been formed on the surface of the lithium metal substrate.
[0094] 2. Assembly of other components and batteries: (1) Positive electrode: NCM811 positive electrode material, conductive carbon black and PVDF are mixed in a mass ratio of 95:2:3, dispersed in NMP to form a slurry, coated on aluminum foil current collector, dried, rolled and cut to obtain the product.
[0095] (2) Separator: Commercial polypropylene / ceramic composite diaphragm.
[0096] (3) The specific composition of the electrolyte is: LiFSI is the electrolyte salt, and DME and TTE are the solvents. According to the molar ratio of LiFSI:DME:TTE=1:1.2:3, a local high-concentration ether-based electrolyte for lithium metal batteries can be prepared.
[0097] (4) Battery assembly: Assemble the soft-pack stacked lithium metal battery in an argon glove box, placing the positive electrode, separator, and negative electrode in sequence, injecting electrolyte, and then sealing.
[0098] Performance testing: (1) Symmetrical battery voltage curve test: Using the prepared lithium-based negative electrodes as both positive and negative electrodes, CR2032 symmetric batteries were assembled. The electrolyte volume was 200 μL, and the separator was a polypropylene / ceramic composite separator. The Blue Electric CT2001A battery testing system was used at 25℃ and 1 mA / cm². 2 Constant current cycling test was performed at current density.
[0099] (2) Cyclic performance test: The prepared lithium-based anodes were used as negative electrodes, and ternary NCM811 was used as positive electrodes, with an active material loading of 20 mg / cm³. 2 Specific capacity per square meter (4mAh / cm²) 2 It is equipped with a 5Ah pouch cell battery. Cyclic testing was conducted using the Blue Electric CT2001A battery testing system at 25℃ under 0.2C charge / 2C discharge conditions, with a voltage range of 3.0~4.3V. Cyclic termination conditions were 500 cycles or a capacity retention rate below 80%. Capacity retention rate = discharge capacity per cycle / first cycle discharge capacity; coulombic efficiency = discharge capacity per cycle / charge capacity.
[0100] (3) Other key parameter tests: The particle size and agglomeration index of the lithiophilic particles were tested using a Malvern Mastersizer 3000 laser particle size analyzer; the agglomeration index and the thickness of the lithiophilic modification layer were tested by cross-sectional observation using a scanning electron microscope (SEM, ZEISS Sigma 300).
[0101] Test results: See Table 1.
[0102] Table 1. Symmetrical battery voltage curves and full-cell cycle performance of Example 1 Example 2 The difference between this embodiment and Example 1 is that the lithiophilic particles are replaced with nano-bismuth, the primary particles have a Dn50 of 170 nm, the secondary particles have a Dn50 of 0.72 μm, the aggregation index is 6, and the specific surface area is 25.2 m². 2 / g; the remaining parameters and preparation process are consistent with those in Example 1.
[0103] Test results: See Table 2.
[0104] Table 2. Symmetrical battery voltage curves and full-cell cycle performance of Example 2 Example 3 The difference between this embodiment and Embodiment 1 is that the lithiophilic particle size is: secondary particle Dn50 = 0.8 μm, agglomeration index = 13, and specific surface area 44.6 m². 2 / g; the remaining parameters and preparation process are consistent with those in Example 1.
[0105] Test results: See Table 3.
[0106] Table 3. Symmetrical battery voltage curves and full-cell cycle performance of Example 3 Example 4 The difference between this embodiment and Embodiment 1 is that the lithiophilic particle size is: secondary particle Dn50 = 0.6 μm, agglomeration index = 3, and specific surface area is 9.2 m². 2 / g; the remaining parameters and preparation process are consistent with those in Example 1.
[0107] Test results: See Table 4.
[0108] Table 4. Symmetrical battery voltage curves and full-cell cycle performance of Example 4 Example 5 The difference between this embodiment and Example 1 is that the weight percentage of lithiophilic particles in the lithiophilic modified layer is 80%, the weight percentage of polymer binder is 10%, and the weight percentage of functional additives is 10%; the remaining parameters and preparation process are the same as in Example 1.
[0109] Test results: See Table 5.
[0110] Table 5. Symmetrical battery voltage curves and full-cell cycle performance of Example 5 Example 6 The difference between this embodiment and Example 1 is that the weight percentage of lithiophilic particles in the lithiophilic modified layer is 95%, the weight percentage of polymer binder is 2.5%, and the weight percentage of functional additives is 2.5%. The remaining parameters and preparation process are completely the same as in Example 1.
[0111] Test results: See Table 6.
[0112] Table 6. Symmetrical battery voltage curves and full-cell cycle performance of Example 6 Example 7 The difference between this embodiment and Embodiment 1 is that the thickness of the lithiophilic modification layer is controlled to 0.36 μm by adjusting the electric field strength, spraying rate and time of electrostatic spraying. The other parameters and preparation process are the same as in Embodiment 1.
[0113] Test results: See Table 7.
[0114] Table 7. Symmetrical battery voltage curves and full-cell cycle performance of Example 7 Example 8 The difference between this embodiment and Embodiment 1 is that the thickness of the modified layer is controlled to 1.82 μm by adjusting the electric field strength, spraying rate and time of electrostatic spraying. The other parameters and preparation process are the same as in Embodiment 1.
[0115] Test results: See Table 8.
[0116] Table 8. Symmetrical battery voltage curves and full-cell cycle performance of Example 8 Example 9 The difference between this embodiment and Example 1 is that the specific composition of the electrolyte is: 1 mol / L LiPF6 as the electrolyte salt, EC and DMC in a volume ratio of 1:1 as the solvent, and 2 wt% FEC as an additive. The remaining parameters and preparation process are consistent with those of Example 1.
[0117] Test results: See Table 9.
[0118] Table 9. Symmetrical battery voltage curves and full-cell cycle performance of Example 9 Comparative Example 1 The difference between this comparative example and Example 1 is that an 80μm thick lithium metal strip is directly selected as the negative electrode, without any lithium-affinity modification layer, while the other parameters and preparation process remain the same as in Example 1.
[0119] Test results: See Table 10.
[0120] Table 10. Symmetrical cell voltage curves and full-cell cycle performance of Comparative Example 1 Comparative Example 2 The difference between this comparative example and Example 1 is that the lithiophilic modified layer does not contain lithiophilic particles, the weight ratio of polymer binder to functional additive is adjusted to 50%:50%, and the remaining parameters and preparation process are the same as in Example 1.
[0121] Test results: See Table 11.
[0122] Table 11. Symmetrical cell voltage curves and full-cell cycle performance of Comparative Example 2 Comparative Example 3 The difference between this comparative example and Example 1 is that the lithiophilic modification layer does not contain a polymer binder, the weight ratio of lithiophilic particles to functional additives is adjusted to 90%:10%, and the remaining parameters and preparation process are the same as in Example 1.
[0123] Test results: See Table 12.
[0124] Table 12. Symmetrical cell voltage curves and full-cell cycle performance of Comparative Example 3 Comparative Example 4 The difference between this comparative example and Example 1 is that the lithiophilic modification layer does not contain functional additives, the weight ratio of lithiophilic particles to polymer binder is adjusted to 90%:10%, and the remaining parameters and preparation process are the same as in Example 1.
[0125] Test results: See Table 13.
[0126] Table 13. Symmetrical cell voltage curves and full-cell cycle performance of Comparative Example 4 Comparative Example 5 The difference between this comparative example and Example 1 is that the functional additive is replaced with a fully saturated organosiloxane, butyltrimethoxysilane, while the remaining parameters and preparation process are the same as in Example 1.
[0127] Test results: See Table 14.
[0128] Table 14. Symmetrical cell voltage curves and full-cell cycle performance of Comparative Example 5 Comparative Example 6 The difference between this comparative example and Example 1 is that the lithiophilic particles are nano-titanium dioxide with Dn50=300nm, while the other parameters and preparation process are the same as in Example 1.
[0129] Test results: See Table 15.
[0130] Table 15. Symmetrical cell voltage curves and full-cell cycle performance of Comparative Example 6 Experimental Results Analysis: When metal oxides are used as lithiophilic particles, the polarization voltage of their symmetric cells is lower than that of metal nitrides. This is because the Li₂O-containing SEI formed on the lithium metal surface by metal oxides has higher ionic conductivity and lower polarization than Li₃N. However, in the full cell, the cycling performance of Comparative Example 6 is slightly worse than that of Example 1, indicating that the SEI formed by metal nitrides is more effective in homogenizing lithium-ion deposition and improving SEI stability.
[0131] At the start of the symmetric cell test, the polarization voltage of each example was in the range of 600-700mV. The polarization voltage of the example with the lithium-loving modification layer was slightly higher, but it decreased rapidly after more than ten hours. At the end of the test, Example 1 performed the best, with a polarization voltage of only 86mV after 2000h and remained stable throughout, showing the best effect. Examples 2-6 and 8 could complete the 2000h test, with a final polarization voltage of 89-110mV, and the polarization voltage growth was moderate. Examples 7 and 9 and Comparative Examples 1-4 showed an abnormally low voltage of about 10mV at 1000-1400h, which was attributed to an internal short circuit caused by lithium dendrite growth. Although Comparative Example 5 completed the 2000h test, its final polarization voltage reached 125mV, showing a significant increase in polarization voltage.
[0132] At the end of the full-cell cycle test, Example 1 showed the best cycle performance, with a capacity retention of 77.8% and a coulombic efficiency of 95.9% after 500 cycles. Examples 2 and 8 could complete 500 cycles, but their capacity retention was slightly lower than that of Example 1. Examples 3 to 6 failed before reaching 500 cycles. Examples 7 and 9 and Comparative Examples 1 to 4 were terminated at 250 to 350 cycles due to excessively rapid performance degradation. Comparative Example 5 failed at around 450 cycles, and its overall performance was inferior to that of Example 1.
[0133] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0134] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0135] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-based anode, characterized in that, Includes a substrate and a lithiophilic modification layer located on at least one surface of the substrate along its thickness direction; The lithiophilic modification layer comprises lithiophilic particles, a polymer binder, and functional additives; The functional additives include organosiloxanes containing unsaturated bonds.
2. The lithium-based anode according to claim 1, characterized in that, The lithium-based anode includes one or more of Si-O-Li bonds, Si-O-Si bonds, and Si-OC bonds; And / or, the peel strength of the lithiophilic modified layer is ≥50 N / m.
3. The lithium-based anode according to claim 1, characterized in that, The lithiophilic particles include one or more of the following: gold, silver, zinc, magnesium, aluminum, platinum, tin, bismuth, antimony, magnesium nitride, aluminum nitride, calcium nitride, titanium nitride, zirconium nitride, vanadium nitride, and tungsten nitride. And / or, the lithium-loving particles comprise secondary particles composed of primary particles; And / or, the polymer binder includes one or more of polyethylene oxide, styrene-butadiene rubber, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, and polyvinyl butyral; And / or, the main chain of the functional additive contains unsaturated bonds; And / or, the functional additive includes an alkoxy group, and the alkoxy group is bonded to a silicon atom.
4. The lithium-based anode according to claim 3, characterized in that, The Dn50 of the secondary particles is 0.6 μm to 0.8 μm; And / or, the Dn50 of the primary particles is 60nm~200nm; And / or, the main chain comprises 2 to 5 carbon atoms; And / or, the silicon atom is bonded to three of the alkoxy groups; And / or, the alkoxy group comprises 1 to 2 carbon atoms.
5. The lithium-based anode according to claim 1, characterized in that, The mass ratio of the lithiophilic particles, the polymer binder, and the functional additive is (80~95):(1~10):(1~10). And / or, the thickness of the lithiophilic modification layer is 0.3 μm to 1.8 μm.
6. The lithium-based anode according to claim 1, characterized in that, The thickness of the substrate is 10μm~100μm; And / or, the substrate comprises metallic lithium or a lithium alloy.
7. A method for preparing a lithium-based anode according to any one of claims 1 to 6, characterized in that, Includes the following steps: A lithiophilic particle, a polymer binder, a functional additive, and an organic solvent are mixed to obtain a lithiophilic modified solution; the functional additive includes an organosiloxane containing unsaturated bonds. The lithiophilic modification solution is coated onto at least one side of the substrate along the thickness direction, and after drying, a lithium-based anode is obtained.
8. The method for preparing a lithium-based anode according to claim 7, characterized in that, Lithophilic particles, polymer binder, functional additives and organic solvent are mixed and stirred at 25℃~55℃ to form a lithiophilic modified solution; the stirring is carried out at a speed of 200rpm~600rpm for 10min~30min. And / or, the solid content of the lithiophilic modified solution is 45%~80%; And / or, the coating includes electrostatic spraying and / or ultrasonic spraying; And / or, the drying includes a first drying and a second drying performed sequentially; the temperature of the first drying is 60℃~100℃ and the time is 20min~60min; the temperature of the second drying is 100℃~120℃ and the time is 10min~30min.
9. A lithium metal battery, characterized in that, Includes the lithium-based anode as described in any one of claims 1 to 6 or the lithium-based anode prepared by the preparation method described in any one of claims 7 to 8.
10. The lithium metal battery according to claim 9, characterized in that, The lithium metal battery further includes an electrolyte; the electrolyte includes an electrolyte salt, a solvent, and additives. Preferably, the electrolyte salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalate borate, and lithium bis(oxalate borate). And / or, the solvent comprises one or more of the following: ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethyl ether, triethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, and fluorinated 1,3-dioxolane; And / or, the additives include one or more of lithium nitrate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl fluorocarbonate, trimethyl phosphate, and triethyl hexafluorophosphate.
Citation Information
Patent Citations
Preparation method of ultrathin lithium metal negative electrode
CN112216811A
Liquid metal coating, preparation method thereof and application of liquid metal coating in lithium-free metal lithium battery
CN114649502A
Three-dimensional porous current collector for lithium battery as well as preparation method and application of three-dimensional porous current collector
CN115347196A